Colonial hymns and Black Spirituals in the context of decoloniality: A theological reflection of Reverand Shadrack Ushewokunze's songs - Martin Mujinga (Pharos Journal of Theology)
Methodist hymns are attributed to Charles Wesley. Most scholars in Methodist studies, theology, and religion have paid attention to his hymns. In contrast, not much attention had been given to hymns by Black Methodists that contributed to the African history, culture, spirituality, and music genres. With ten hymns, Reverend Ushewokunze tops the list of songs by the Black Methodists, and yet there is no scholarly literature that theologises his hymns written during the colonial era. Using the decolonial framework and qualitative methodology, this paper aims to argue that Ushewokunze’s hymns represent the spirituals of the Black Christians in Zimbabwe and how they used songs to respond to their spiritual suffocation. Ushewokunze’s composition of hymns at the height of the colonial era underscores the experiences of the Black Christians which they expressed through spirituals as a tool of decoloniality. The paper defined colonial hymns and Black spirituals. It also presents the historical background of Reverend Ushewokunze and how these humble beginnings had a bearing on the writings of his songs. The paper calls for a re-engagement of Black spirituals to appreciate how the native Christians used songs to contextualise worship. It concluded by recommending the Methodist Church in Zimbabwe and other mainline churches to deliberate use of the hymns by Black singers to unpack their theology in the African religio-cultural experiences of the colonial era.